Eksistensi Putusan Mahkamah Konstitusi Pasca Disahkannya Undang-Undang Penetapan Perpu Cipta Kerja - Yohanes Suhardin; Henny Saida Flora (Jurnal USM Law Review)
This study aims at analyzing the existence of Constitutional Court Ruling No. 91/PUU-XVIII/2020 (Job Creation MK Decision) after Law No. 6 of 2023 concerning Job Creation. This research is a normative legal research by prioritizing case approaches, concepts, and legislation. The results of the study confirmed that the existence of the Job Creation MK Decision after the passage of the Job Creation Law was as if the Job Creation MK Decision was between "there and not". It is said that there is because it is used as a juridical basis in the Job Creation Law, however substantively the Decision of the Job Creation MK, especially the constitutional order to substantively improve the Job Creation Law by involving meaningful community participation, has not been implemented. Because, the government (in this case the President) actually uses the Job Creation Law instrument which substantively denies the Job Creation MK Decision. The legal implications of the Job Creation MK Decision after the Job Creation Law was passed is that the Job Creation Law has actually violated the substance of the Job Creation MK Decision. It can be seen that the Job Creation MK Decision orients the reformulation of the Job Creation Law through meaningful participation involving all components of society. The existence of disobedience to the Job Creation Law against the Decision of the Job Creation MK has the potential to cause a phenomenon of disregard for the constitution (constitutional disobedience). Therefore, in the future it is necessary to formulate the forms and types of sanctions against the Constitutional Court's Decision and also be oriented to the Constitutional Court being able to review a Law or UU that contradicts the Constitutional Court's Decision.